Epigenetic DNA Methylation Mediating Octopus vulgaris Early Development: Effect of Essential Fatty Acids Enriched Diet - García-Fernández, Pablo; García-Souto, Danie; Almansa, Eduardo; Morán, Paloma; Gestal, Camino (Frontiers in Physiology, 2017)
The common octopus, Octopus vulgaris, is a good candidate for aquaculture but a sustainable production is still unviable due to an almost total mortality during the paralarvae stage. DNA methylation regulates gene expression in the eukaryotic genome, and has been shown to exhibit plasticity throughout O. vulgaris life cycle, changing profiles from paralarvae to adult stages. This pattern of methylation could be sensitive to small alterations in nutritional and environmental conditions during the species early development, thus impacting on its health, growth and survival. In this sense, a full understanding of the epigenetic mechanisms operating during O. vulgaris development would contribute to optimizing the culture conditions for this species. Paralarvae of O. vulgaris were cultured over 28 days post-hatching (dph) using two different Artemia sp. based diets: control and a long chain polyunsaturated fatty acids (LC-PUFA) enriched diet. The effect of the diets on the paralarvae DNA global methylation was analyzed by Methyl-Sensitive Amplification Polymorphism (MSAP) and global 5-methylcytosine enzyme-linked immunosorbent assay approaches. The analysis of different methylation states over the time revealed a global demethylation phenomena occurring along O. vulgaris early development being directly driven by the age of the paralarvae. A gradual decline in methylated loci (hemimethylated, internal cytosine methylated, hypermethylated) parallel to a progressive gain in non-methylated loci towards the later sampling points was verified regardless of the diet provided and demonstrate a pre-established and well-defined demethylation program during its early development, involving a 20% of the MSAP loci. In addition, a differential behavior between diets was also observed at 20 dph, with a LC-PUFA supplementation effect over the methylation profiles. The present results show significant differences on the paralarvae methylation profiles during its development and a diet effect on these changes. It is characterized by a process of demethylation of the genome at the paralarvae stage and the influence of diet to favor this methylation loss.